1995
DOI: 10.1111/j.1365-2044.1995.tb15095.x
|View full text |Cite
|
Sign up to set email alerts
|

The intensive care treatment of convulsive status epilepticus in the UK

Abstract: Summary Six hundred and ninety-four members of the Intensive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 43 publications
(14 reference statements)
0
28
0
2
Order By: Relevance
“…Many intensive-care units in Britain continue to prefer phenobarbitone as the barbiturate for children 25 . Pentobarbital tends to be the barbiturate of choice in USA.…”
Section: Barbituratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many intensive-care units in Britain continue to prefer phenobarbitone as the barbiturate for children 25 . Pentobarbital tends to be the barbiturate of choice in USA.…”
Section: Barbituratesmentioning
confidence: 99%
“…Thiopentone is the favoured barbiturate in the treatment of refractory CSE but needs to be used in the ITU and with particular care in patients with impaired myocardial function 25 . Many intensive-care units in Britain continue to prefer phenobarbitone as the barbiturate for children 25 .…”
Section: Barbituratesmentioning
confidence: 99%
“…Propofol has been reported to have antiepileptic activity in humans (20)(21)(22)(23)(24)(25)(26)(27), and several case reports describing its use in SE have been published (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In a study (4) of members of the Intensive Care Society in the United Kingdom, 12% indicated that propofol was their second-line choice for management of SE despite suggestions that propofol may have a proconvulsant effect (30,3 1).…”
mentioning
confidence: 99%
“…Third, many patients with RSE manifest only subtle signs of seizure activity and thus are not diagnosed. For these reasons, many different protocols are used in treating RSE (4). One of the most frequently used and the best studied protocol in the United States involves use of high-dose barbiturates (9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…midazolam (MDL) (1,8,9) or continuous i.v. propofol (PRO) (10,11) as alternatives to phenobarbital (PB) or continuous i.v. pentobarbital (PTB), evidence for this treatment practice is largely anecdotal.…”
mentioning
confidence: 99%